Fano Resonance in a Metasurface Composed of Graphene Ribbon Superlattice - Zi-Lan Deng; Xiangping Li; Tao Fu; Guo Ping Wang (IEEE Photonics Journal)
We present a metasurface composed of graphene ribbon superlattice that supports plasmonic Fano resonance in a simple symmetric configuration. Without the necessity of changing the geometry size of graphene ribbons, we tune the Fano resonance of the metasurface containing identical graphene ribbons by simply changing the global or local periods of the superlattice. The increase of the global period of the superlattice leads to a blue-shift of the broad resonance of the bright mode, while the increase of the local period leads to simultaneous shifts of the broad resonance of the bright mode and the sharp resonance of the dark mode toward opposite direction with respect to each other. The resonance shift mechanism can be well explained by the restoring force model for longitudinal dipole arrays. In addition, the overall spectral position of the Fano resonance can be actively tuned by the fermi level of graphene ribbons. Our methods provide a simple and flexible pathway to tune the plasmonic Fano resonance, which holds great potentials for tunable biosensing and slow light applications with improved performance.